Isotope shift of 40, 42, 44, 48Ca in the 4s 2S1/2 → 4p 2P3/2 transition. (13th November 2015) - Gorges, C; Blaum, K; Frömmgen, N; Geppert, Ch; Hammen, M; Kaufmann, S; Krämer, J; Krieger, A; Neugart, R; Sánchez, R; Nörtershäuser, W
Abstract: We report on improved isotope shift measurements of the isotopes Ca in the (D2) transition using collinear laser spectroscopy. Accurately known isotope shifts in the (D1) transition were used to calibrate the ion beam energy with an uncertainty of The accuracy in the D2 transition was improved by a factor of 5–10. A King-plot analysis of the two transitions revealed that the field shift factor in the D2 line is about 1.8(13)% larger than in the D1 transition which is ascribed to relativistic contributions of the wave function.